Chemopreventive effect of troxerutin against hydrogen peroxide-induced oxidative stress in human leukocytes through modulation of glutathione-dependent enzymes. Issue 4 (16th February 2021) - Cavalcanti, Bruno Coêlho; Neto, João Batista de Andrade; Silva, Antônio Adailson de Sousa; Barreto, Francisco Stefânio; Ferreira, José Roberto de Oliveira; Magalhães, Hemerson Iury Ferreira; Silva, Cecília Rocha da; Vieira, Ícaro Gusmão Pinto; Ricardo, Nágila Maria Pontes Silva; Nobre Júnior, Hélio Vitoriano; Moraes, Manoel Odorico
ABSTRACT: Troxerutin is a natural flavonoid present abundantly in tea, coffee, olives, wheat, and a variety of fruits and vegetables. Due to its diverse pharmacological properties, this flavonoid has aroused interest for treatment of various diseases, and consequently prompted investigation into its toxicological characteristics. The aim of this study was to evaluate the genotoxic and mutagenic effects and chemoprotective activity attributed to troxerutin using human peripheral blood leukocytes (PBLs) through several well-established experimental protocols based upon different parameters. Data demonstrated that troxerutin (100 to 1000 µM) induced no marked cytotoxic effect on PBLs after 24 hr, and did not produce strand breaks and mutagenicity. Regarding chemoprevention, this flavonoid attenuated cytotoxicity, genotoxicity, and mutagenicity initiated by hydrogen peroxide (H2 O2 ) in human PBLs. Further, troxerutin demonstrated no marked cytotoxic effect on PBLs and exerted a protective effect against oxidative stress induced by H2 O2 through modulation of GSH-dependent enzymes.